2016
DOI: 10.3109/10903127.2015.1128033
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prehospital Tranexamic Acid Administration Protocol

Abstract: Prehospital TXA protocol based on the CRASH-2 trial is safe and feasible. The first dose of TXA administered under this protocol marks the first ground EMS administration in the USA. Conceivably, this will pose as a model to other trauma centers that receive patients from outlying areas without immediate access to care. Large multi-institutional analyses need to be performed to evaluate survival benefits of prehospital TXA administration protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…In our small study, we have shown that nurses working in an emergency centre setting can identify suitable patients and safely administer TXA to a similar level described in the prehospital literature [17] .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In our small study, we have shown that nurses working in an emergency centre setting can identify suitable patients and safely administer TXA to a similar level described in the prehospital literature [17] .…”
Section: Discussionmentioning
confidence: 61%
“…As the benefit of TXA is being increasingly recognised, strategies to deliver it to bleeding patients have been developed. The first step was inclusion into hospital major haemorrhage protocols, and as the importance of early administration became more apparent, prehospital usage has followed [17] , [18] , [19] . However, these strategies have all generally trickled down from high-income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was also reported that pharmacist intervention did not increase adherence to guideline‐directed statin therapy, and pharmacist intervention did not significantly affect prescribers' adherence rate to the 2013 American college of cardiology/American heart association cholesterol guideline . To the best of our knowledge, no pharmacist‐led intervention on TXA treatment has been reported, besides one pre‐hospital administration protocol where the pharmacist was responsible for expediting the delivery of TXA to the trauma bay …”
Section: Introductionmentioning
confidence: 94%
“…10,11 Nevertheless, the current European Trauma Treatment Guidelines recommend the early use of TXA in bleeding trauma patients. 12 In addition, up to now, only few retrospective studies on the prehospital use of TXA exist [13][14][15] and the exact mechanism of action of early TXA administration in trauma patients is insufficiently known.…”
mentioning
confidence: 99%